2017
DOI: 10.3389/fmicb.2017.00048
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Uses Specific Domain Rearrangements and Allelic Exchange to Generate Diversity in Surface Virulence Factors

Abstract: Porphyromonas gingivalis is a keystone pathogen of chronic periodontitis. The virulence of P. gingivalis is reported to be strain related and there are currently a number of strain typing schemes based on variation in capsular polysaccharide, the major and minor fimbriae and adhesin domains of Lys-gingipain (Kgp), amongst other surface proteins. P. gingivalis can exchange chromosomal DNA between strains by natural competence and conjugation. The aim of this study was to determine the genetic variability of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 107 publications
(141 reference statements)
2
52
1
4
Order By: Relevance
“…Strain 33277 represents the fimbriated/nonencapsulated lineage and possesses both the Mfa1 and FimA fimbriae, which are present in 20 of 21 P. gingivalis strains. Strain W83 represents the nonfimbriated/capsulated lineage . Both strains are pathogenic in animal models of infection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain 33277 represents the fimbriated/nonencapsulated lineage and possesses both the Mfa1 and FimA fimbriae, which are present in 20 of 21 P. gingivalis strains. Strain W83 represents the nonfimbriated/capsulated lineage . Both strains are pathogenic in animal models of infection .…”
Section: Discussionmentioning
confidence: 99%
“…Strain W83 represents the nonfimbriated/capsulated lineage. (32) Both strains are pathogenic in animal models of infection. (33) Detection of the antibodies showed a wide range of concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis exchanges chromosomal DNA between strains by natural competence and conjugation [68]. By using antibiotic resistance markers, it was demonstrated that the strains ATCC 33277 T and W83 of P. gingivalis were able to exchange chromosomal DNA resulting in offspring, which carried DNA from both donor and recipient [6].…”
Section: Introductionmentioning
confidence: 99%
“…A high level of reticulation was seen in the phylogenetic networks constituted by 23 strains of P. gingivalis [8]. This indicated extensive horizontal gene transfer between the strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation